Study of an Oxygenated Heme Complex in Frozen Solution by Mössbauer Emission Spectroscopy - Marchant, Linda (1972)
We have used Mössbauer emission spectroscopy to study an oxygenated heme complex, produced in a frozen solution by nuclear decay from the isomorphous (57)Co-labeled compound. The Mössbauer parameters agree with those obtained by Mössbauer absorption spectroscopy of oxyhemoglobin. Thus, a nonprotein environment for iron can duplicate the unique oxyhemoglobin Mössbauer spectrum. The electronic structure of the heme iron in oxyhemoglobin is not significantly influenced by the protein environment. Mössbauer emission spectroscopy can be useful in the investigation of heme proteins.